Sistem Pendukung Keputusan Pemilihan Foundation Makeup Menggunakan Metode Fuzzy Berbasis Mobile - Ferjenia Feybelia; Ferdinan Sangkop; Kristofel Santa (Program Studi Teknik Informatika, 2026)
Choosing a cosmetic is not easy, most buyers only see advertisements and promos, without reading the ingredients contained in the product that cause itching, irritation, and pimples on the face because the product is not suitable for the type of facial skin. For that, an application is needed to support the decision making of foundation makeup that is suitable for the type of facial skin to make it easier to find foundation products. This system helps users to support their decisions by recommending products that are suitable for the skin type of each individual who has different types of facial skin ranging from dry, normal, and oily skin. The purpose of this research is to design a decision support system application that will make it easier for users to find foundation makeup products according to the needs of the skin. Fuzzy Logic Method (Fuzzy Logic) was first introduced by Prof. Lotfi A. Zadeh in 1965. The basis of Fuzzy Logic is the theory of Fuzzy sets. In Fuzzy set theory, the role of disclosure level as a determinant of the existence of elements in a set is very important. The expected results can help make-up beginners or customers to choose a foundation that suits their skin type.